Clinical observation on the early rehabilitation outcomes of the first-time artificial total hip arthroplasty using the direct anterior approach (首次人工全髋关节置换术直接前方入路的早期康复效果观察) - FANG Lamei (方腊梅); JIN Yanyan (金艳艳); WEI Xiuduo (魏修朵); LIU Qin (刘琴) (Journal of International Translational Medicine Limited, 2024)
Objective To observe the early rehabilitation outcomes of the first-time artificial total hip arthroplasty (THA) using the direct anterior approach (DAA). Methods Sixty patients who underwent unilateral THA for the first time at Huangshan People's Hospital from 2020 to 2021 were selected, including 30 cases of THA using the direct anterior approach (DAA group) and 30 cases of THA using the posterior-lateral approach (PLA group). The surgical incision length, intraoperative blood loss, duration of drainage tube placement, time to first ambulation after surgery, quality of life, complications, pain, and joint function recovery were compared between the two groups. Pain was assessed using the Visual Analog Scale (VAS) at 1 week, 4 weeks, and 12 weeks postoperatively. Hip joint function was evaluated using the Harris Hip Score (HHS) scoring system, and quality of life was assessed using the S-36 questionnaire. Results The DAA group had a shorter incision length and less intraoperative blood loss compared to the PLA group, and time to first ambulation was earlier and duration of drainage tube placement was shorter in the DAA group compared to the PLA group, with a significant difference (P＜0. 05). At 4 and 12 weeks postoperatively, pain VAS scores, Harris scores, and quality of life were higher in the DAA group compared to the PLA group, with a significant difference (P＜0. 05). There was a case of dislocation of hip prosthesis and a cased of periprosthesis infection in the PLA group, and no postoperative complications reported in the DAA group. Conclusion Compared with PLA approach, THA using the DAA approach results in smaller trauma and faster recovery, aligning with the concept of rapid rehabilitation and showing better clinical efficacy. (目的 探讨首次人工全髋关节置换术(THA)直接前方入路(DAA)的早期临床康复效果。方法 选取2020年1月-2021年12月在黄山市人民医院首次接受单侧THA的患者60例, 其中直接前方入路(DAA)THA 30例(DAA组), 后外侧入路(PLA)THA 30例(PLA组)。比较两组患者手术切口长度、术中出血、引流管留置时间、术后首次下床时间、生活质量、并发症、疼痛及关节功能恢复情况, 在术后1周、术后4周、术后12周应用视觉模拟量表(VAS)评价疼痛, 应用Harris髋关节评分系统(HHS)评价髋关节功能, 应用健康调查简易量表(SF-36)评价生活质量。结果 DAA组切口长度、术中出血量少于PLA组, 首次下床时间早于PLA 组, 引流管留置时间短于PLA 组, 差异有统计学意义(P＜0. 05)。DAA组患者术后4周、术后12周疼VAS评分、Harris评分、SF-36量表评分均高于PLA组, 差异有统计学意义(P＜0. 05); PLA组术后出现1例髋关节假体脱位, 1例出现假体周围感染; DAA组无并发症发生。结论 与PLA比较, DAA入路行THA创伤更小, 恢复更快, 符合快速康复理念, 早期临床康复效果更佳。)